Development of the Android-Based “NADA” (Napas Diafragma) Application Strategy for People of Productive Age Towards Mentally Healthy Indonesia - Bernadus Sadu; Maria Silvana Dhawo; Utomo Wicaksono (Institute of Computer Science (IOCS), 2022)
The pandemic that hit caused the stress level of the productive age group to increase, which would hamper the President's vision in 2024 in the health sector to create a productive Indonesian society. One inexpensive, easy, and convenient exercise to facilitate relaxation in the midst of stress is breathing exercises. However, it is necessary to explore the level of community needs and how to get breathing exercises easily. Technology is one of the means to facilitate the community in improving health. Starting from this, this study will develop an android-based diaphragmatic breathing application for people of productive age as an effort to apply technology in the health sector.